Cardiac contractility modulation in heart failure with reduced ejection fraction patients with QRS duration 120-149 ms: reduction in heart failure hospitalizations and improvement in functional outcome - Fastner, Christian; Varma, Niraj; Rao, Ishu; Falk, Peter; Remppis, Bjoern Andrew; Najarian, Kevin; Burkhoff, Daniel; Akın, Ibrahim; Kuschyk, Jürgen (Heart rhythm, 2025)
Background - A subset of heart failure with reduced ejection fraction (HFrEF) patients qualifies for cardiac resynchronization therapy (CRT). However, a 30% CRT nonresponder rate persists, with patients having narrower QRS durations (ie, QRSd 120-149 ms) receiving less or inconsistent benefit. Cardiac contractility modulation (CCM) may be an important alternative therapy option but has largely been evaluated only in HFrEF patients with QRSd <120 ms. - Objectives - The purpose of this study was to evaluate the impact of CCM on HF-related hospitalizations and on left ventricular ejection fraction (LVEF) as well as quality of life in HFrEF patients with QRSd 120-149 ms compared to QRSd <120 ms. - Methods - The CCM-REG Registry enrolled a total of 503 HFrEF patients with follow-up up to 2 years. Hospitalization rates were available for 1 year preimplant. Safety was assessed by comparison of actual vs Meta-Analysis Global Group in Chronic Heart Failure (MAGGIC) risk score- or Seattle Heart Failure Model (SHFM)-predicted mortality. - Results - Among 111 of 455 patients with QRSd 120-149 ms (mean QRSd 130 ± 9 ms; 20% female; age 68 ± 11 years; LVEF 29% ± 9%; 82% New York Heart Association [NYHA] class III), CCM diminished HF-related hospitalization rate by 72% (pre- vs postimplant 0.90 vs 0.25 events per patient-year over 2 years; P <.001). LVEF improved by 7% ± 9% (P = .014 vs baseline), Minnesota Living with Heart Failure Questionnaire score by 10 ± 23 points (P = .010 vs baseline), and NYHA class by 0.5 ± 0.7 classes (<0.001 vs baseline). The effect sizes were similar to those in QRSd <120 ms patients. Mortality within the first year was 19% in QRSd 120-149 ms patients (ie, not significantly different from the MAGGIC risk score or SHFM prediction). - Conclusions - CCM significantly improved HF control in NYHA class III HFrEF with reduced ejection fraction patients with moderately prolonged QRSd of 120-149 ms. The effect was comparable to that in patients with QRSd <120 ms.